2016
DOI: 10.1016/j.ccell.2016.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles in Cancer: Cell-to-Cell Mediators of Metastasis

Abstract: Summary Tumor-secreted extracellular vesicles (EVs) are critical mediators of intercellular communication between tumor cells and stromal cells in local and distant microenvironments. Accordingly, EVs play an essential role in both primary tumor growth and metastatic evolution. EVs orchestrate multiple systemic pathophysiological processes, such as coagulation, vascular leakiness, and reprogramming of stromal recipient cells to support pre-metastatic niche formation and subsequent metastasis. Clinically, EVs m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
1,281
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,520 publications
(1,374 citation statements)
references
References 149 publications
11
1,281
0
5
Order By: Relevance
“…Exosomes are vesicles of 50-100 nm in size that are over-produced by most proliferating cell types during normal states, pathological states (such as cancer), and states such as pregnancy. Exosomes contain a wide variety of proteins, lipids, RNAs, non-transcribed RNAs, miRNAs, and small RNAs (Yin et al, 2013;Becker et al, 2016). Ongoing efforts have shown that miRNAs are secreted into tumor microenvironments to regulate cancer cell proliferation, migration, immune response, intercellular communication, and stromal modification, thereby promoting tumor growth and progression (Meckes et al, 2010;Zhang et al, 2015b;Li et al, 2016).…”
Section: Ebv Regulates the Inflammatory Tumor Microenvironment Via MImentioning
confidence: 99%
“…Exosomes are vesicles of 50-100 nm in size that are over-produced by most proliferating cell types during normal states, pathological states (such as cancer), and states such as pregnancy. Exosomes contain a wide variety of proteins, lipids, RNAs, non-transcribed RNAs, miRNAs, and small RNAs (Yin et al, 2013;Becker et al, 2016). Ongoing efforts have shown that miRNAs are secreted into tumor microenvironments to regulate cancer cell proliferation, migration, immune response, intercellular communication, and stromal modification, thereby promoting tumor growth and progression (Meckes et al, 2010;Zhang et al, 2015b;Li et al, 2016).…”
Section: Ebv Regulates the Inflammatory Tumor Microenvironment Via MImentioning
confidence: 99%
“…Large cells membrane-derived extracellular vesicles (EVs), known as microparticles (MPs) and microvesicles (MVs), have been reported to play a role in the horizontal communication between cells [129] . Hepatocytes secrete exosomes, MPs and MVs, and their production can change quantitatively and qualitatively in response to cellular stimulation and under different disease conditions [130] .…”
Section: Tumor-associated Circulating Microparticlesmentioning
confidence: 99%
“…They have been shown to transfer RNAs and proteins that are functional in the recipient cells (15,16). They can be found in various body fluids and in the tumour microenvironment and can transmit messages to neighbouring cells as well as to distant cells (17,18). miRNAs, short non-coding RNAs whose levels can be altered during stress response (19), can also be shuttled between cells in the tumour microenvironment via EVs.…”
mentioning
confidence: 99%